ASSESSMENT OF ANTIOXIDANT ACTIVITIES, PHENOL AND FLAVONOID CONTENTS OF DIFFERENT EXTRACTS OF LEAVES, BARK AND ROOT FROM THE Abutilon indicum (L.) SWEET - D, Saranya; J, Sekar; Raj G, ADAIKALA (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: This study evaluated the antioxidant properties of petroleum ether, chloroform, ethyl acetate and methanol extracts of Abutilon indicum (L). Methods: The different extracts of A. indicum leaves, bark and roots were antioxidant potential by using 1,1-diphenyl-2-picryl-hydrazyl (DPPH), 2, 2-Azino-bis-3-ethyl benzthiazoline-6-sulphonic acid (ABTS•+) , Hydrogen peroxide scavenging, Superoxide anions scavenging, Hydroxyl radical scavenging, Ferric reducing antioxidant power, Total antioxidant activity (Phosphomolybdic acid) and total phenol and flavonoid contents. Results: The highest total phenol and flavonoid contents in leaves extracts of A. indicum. The total phenol (3.08 ± 0.06) mg/ml and flavonoid (7.16 ± 0.15) mg/ml were found to be higher in ethyl acetate extract of A. indicum and free radical scavenging activities IC50 values were calculated and compare to standard for L- ascorbic acid, (BHT) butylated hydroxytoluene and gallic acid Conclusion: The results of the study revealed that the ethyl acetate extract of A. indicum leaves can be used for the biological characterization and importance of the compounds identified and creates a platform to screen many bioactive compounds to treat many diseases. Keywords: Abutilon indicum, Free radical scavenging activity, 1,1-diphenyl-2-picryl-hydrazyl, 2-azino-bis-3-ethyl benzthiazoline-6-sulfonic acid, Ferric reducing antioxidant power.